Occupational Stress among Secondary School Heads: A Gender Based Comparative Study (Journal of Education and Educational Development, 2020)
The purpose of the study was to examine and compare the occupational stress of male and female secondary-school-heads in Khyber Pakhtunkhwa. All the male and female secondary school heads working in pubic secondary schools of Khyber Pakhtunkhwa constituted the population of the study. A total of 402 secondary school heads were selected as sample through multistage sampling technique in which 260 were males and 142 were females. Descriptive and quantitative survey research design was used. To seek the responses from the participants, a standardized tool i.e., “Occupational Stress Index (OSI)” was used. For statistical analysis, proper descriptive statistics i.e., mean, standard deviation and inferential statistics i.e., independent samples t-test were employed through SPSS. The findings revealed that both male and female secondary school heads were found occupationally stressful with respect to role overload, role conflict, strenuous working condition, unreasonable group & political pressure, under participation, and unprofitability. Comparatively, there was no significant difference between the overall occupational stress of male and female secondary school heads. Based on findings, it was recommended that Elementary & Secondary Education Department should have a collaboration with policymakers to develop comprehensive strategies for stress reduction for secondary school heads so that they may perform their duties effectively.